Influence of Age and Eosinophilic Esophagitis on Esophageal Distensibility in a Pediatric Cohort. (September 2017) - Menard‐Katcher, Calies; Benitez, Alain J; Pan, Zhaoxing; Ahmed, Faria N; Wilkins, Benjamin J; Capocelli, Kelley E; Liacouras, Chris A; Verma, Ritu; Spergel, Jonathan M; Furuta, Glenn T; Muir, Amanda B
Abstract : Objectives: Sequelae of eosinophilic esophagitis (EoE) include food impaction and esophageal stricture. Duration of inflammation is a predicted risk factor; however, complications remain unpredictable. Studies using the functional lumen imaging probe (FLIP) have demonstrated decreased distensibility of the esophagus in adult patients with EoE. As the impact of inflammation on the developing esophagus is unknown, we investigated esophageal distensibility in a pediatric cohort to determine the effect of age, ongoing inflammation, and fibrotic features on distensibility. Methods: We conducted a prospective observational study at two tertiary pediatric institutions. Subjects underwent FLIP evaluation during endoscopy to determine distensibility of the esophagus. During stepwise distension, simultaneous intrabag pressure and 16 channels of cross‐sectional areas were measured. The minimal diameter at maximal esophageal distention at an intrabag pressure of 40 mm Hg was identified. Distensibility was compared between EoE and non‐EoE subjects and between clinical variables within the EoE cohort. Potential confounding variables were identified. Results: Forty‐four non‐EoE and 88 EoE subjects aged 3–18 years were evaluated. Age positively correlated with esophageal distensibility in the non‐EoE cohort, but this trend was not observed in the EoE population. Subjects with EoE had reduced distensibility even after adjusting for age. Active inflammation (eosinophils >15 eos/high‐power field), histological lamina propria fibrosis, and various features of a fibrotic phenotype (stricture, food impaction, circumferential rings on endoscopy) were associated with decreased distensibility within the EoE cohort. FLIP was safe, feasible, and well tolerated. Conclusions: These findings suggest that remodeling occurs in the pediatric EoE population, warranting early diagnosis and initiation of therapy prior to the onset of disease complications.